PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS CANVA DALAM MENDUKUNG LITERASI DIGITAL SISWA SMA PADA PEMBELAJARAN PAI - Wisnu Legial Barokah; Aulya Rahmadhani Harahap; Bella Saputri; Marsya Dwianda; Nurul Mahfuza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Advances in digital technology have brought about changes in the teaching of Islamic Religious Education (IRE). One digital tool that can be utilised is Canva, a graphic design platform that helps teachers present material in an engaging, interactive and creative manner. This study aims to analyse the use of Canva in supporting the digital literacy of senior secondary school students in Islamic Religious Education. The study employs a descriptive qualitative method using a literature review approach. Furthermore, Canva has the potential to create more innovative Islamic Religious Education lessons that align with the demands of 21st-century education. However, the implementation of Canva in learning still faces various challenges, such as limited digital literacy, internet constraints, the depth of the material, and Islamic digital ethics. Therefore, training and the reinforcement of Islamic values are required so that the use of Canva can run optimally in PAI learning.